2021
DOI: 10.3389/fpls.2021.649304
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Fertigation of Soilless Urban Vertical Agriculture Through the Combination of Struvite and Rhizobia Inoculation in Phaseolus vulgaris

Abstract: Soilless crop production is a viable way to promote vertical agriculture in urban areas, but it relies extensively on the use of mineral fertilizer. Thus, the benefits of fresher, local food and avoiding the transportation and packaging associated with food import could be counteracted by an increase in nutrient-rich wastewater, which could contribute to freshwater and marine eutrophication. The present study aimed to explore the use of mineral fertilizer substitutes in soilless agriculture. Phaseolus vulgaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In a study with common bean, plants in the treatment groups inoculated with Rhizobia spp. and irrigated with a N-free nutrient solution sustained no signs of N-deficiency throughout the growth cycle [ 58 ]. Another study with hydroponic bean found that a rhizobial inoculation led to the successful nodulation and sustenance of normal N levels in tissue, but only when the inorganic N supply was restricted [ 59 ].…”
Section: Plant-associated Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…In a study with common bean, plants in the treatment groups inoculated with Rhizobia spp. and irrigated with a N-free nutrient solution sustained no signs of N-deficiency throughout the growth cycle [ 58 ]. Another study with hydroponic bean found that a rhizobial inoculation led to the successful nodulation and sustenance of normal N levels in tissue, but only when the inorganic N supply was restricted [ 59 ].…”
Section: Plant-associated Bacteriamentioning
confidence: 99%
“…Another study with hydroponic bean found that a rhizobial inoculation led to the successful nodulation and sustenance of normal N levels in tissue, but only when the inorganic N supply was restricted [ 59 ]. In both of these studies, complications with cation uptake (resulting from the absence of the NO 3 − anion from the nutrient solution) led to smaller plants in general, but the N demand was satisfied [ 58 , 59 ]. For N-fixing bacteria to gain a more widespread commercial use in soilless systems, electrochemical imbalances resulting from reduced-N nutrient solutions should be resolved, and applications to non-leguminous plants—specifically, common hydroponic plants such as lettuce, tomato, and other leafy greens—should be further researched and developed.…”
Section: Plant-associated Bacteriamentioning
confidence: 99%
“…Despite this potential, only a small number of research studies have been conducted aiming to optimise BNF and minimise mineral-N application to the common bean grown in soilless systems [ 27 ]. A range of mineral-N application levels, in combination with rhizobia inoculation in the hydroponically cultivated common bean was evaluated by Kontopoulou et al [ 28 ] and Arcas-Pilz et al [ 29 ]. However, given the severe N starvation applied in both studies, BNF capacity was too low to meet the plant requirements, and so yield and profitability were compromised.…”
Section: Introductionmentioning
confidence: 99%
“…There is already a move from traditional farming systems to protected farming systems mainly soilless farming [4] . Fresh farming systems to produce vegetables specifically while reducing land use are being exploited [5] . Some studies have already shown soilless culture to be an alternative cropping system to traditional farming in terms of reducing the problems related to conventional farming such as; low profitability [6] .…”
Section: Introduction and Study Rationalementioning
confidence: 99%
“…The purpose of this study was to develop a simplified low-cost vertical hydroponic unit to increase vegetable production within urban centers in developing states that still have low adoption of soilless farming technologies and yet battling with food insecurity challenges. Soilless farming is a sustainable method for supporting vertical agriculture in urban areas [5] . Vertical farming in itself has the capacity to produce food in a climate-resilient way while using low land as compared to traditional soil culture systems.…”
Section: Introduction and Study Rationalementioning
confidence: 99%